Phlebosclerotic colitis mimicking colon cancer - Yoo, Chang Hun; Kim, Jae Hyun; Kwon, Hye Jung; Moon, Won; Park, Seun Ja; Park, Moo In; Kim, Sung Eun; Park, Jung Gu; Chang, Hee Kyung (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Yoo CH, Kim JH, Kwon HJ, et al. Phlebosclerotic colitis mimicking colon cancer. Turk J Gastroenterol 2017; 28: 37-9.